2003
DOI: 10.1109/jmems.2003.820285
|View full text |Cite
|
Sign up to set email alerts
|

Digitally Tunable Microfluidic Optical Fiber Devices

Abstract: This communication introduces a digital design for tunable microfluidic optical fiber devices. In these systems, multiple, independently controlled microfluidic plugs are pumped into or out of overlap with a fiber structure to modulate its transmission characteristics. The devices described here use eight plugs, eight electrowetting pumps and a corresponding set of molded planar recirculating microchannels to control the depth of the narrowband loss feature associated with a long period fiber grating. Optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 8 publications
0
31
0
Order By: Relevance
“…The equations for the pressure field are (13) (14) where is the Laplacian operator, denotes the domain of the liquid droplet in two dimensions, is its boundary, is the pressure, is a chosen length scale, is the channel height, and is the curvature in the -plane. The curvature, , is given by (15) where and are the contact angles on the top and bottom of the EWOD device, respectively.…”
Section: Final Equation Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…The equations for the pressure field are (13) (14) where is the Laplacian operator, denotes the domain of the liquid droplet in two dimensions, is its boundary, is the pressure, is a chosen length scale, is the channel height, and is the curvature in the -plane. The curvature, , is given by (15) where and are the contact angles on the top and bottom of the EWOD device, respectively.…”
Section: Final Equation Summarymentioning
confidence: 99%
“…Applications for these devices range from microfluid transport [9], mixing [10], dispensing [11], and "lab-on-a-chip" devices that automate functions like sensing and testing of biological samples [12], [13] to tunable optical fiber devices [14], [15] and reflective displays [16].…”
Section: Introductionmentioning
confidence: 99%
“…Similar strategy has been tested by us previously to independently pump multiple microfluidic plugs into or out of overlap with an optical fiber, allowing for a variety of different configurations to modulate the fiber transmission. [25] In a separate effort, we have fabricated soft lenses from hydrogels, which could change the shape, volume and refractive index continuously in response to external stimuli (pH, temperature, etc. ).…”
Section: Variable Transmission Using Dye-containing Solutionsmentioning
confidence: 99%
“…To avoid electrolysis, an insulating layer is usually inserted between the droplet and electrodes [4]- [6]. The applications of EWOD devices were discussed extensively in the literature, including microfluid transport [7], tunable optical fiber devices [8], rotating liquid micromotor [9], micro-injection [10], particle separation and concentration control [11]. Other studies focusing on the modeling of EWOD devices can be found in [3,5,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%